2008
DOI: 10.1091/mbc.e07-12-1286
|View full text |Cite
|
Sign up to set email alerts
|

Apical Accumulation of Rho in the Neural Plate Is Important for Neural Plate Cell Shape Change and Neural Tube Formation

Abstract: Although Rho-GTPases are well-known regulators of cytoskeletal reorganization, their in vivo distribution and physiological functions have remained elusive. In this study, we found marked apical accumulation of Rho in developing chick embryos undergoing folding of the neural plate during neural tube formation, with similar accumulation of activated myosin II. The timing of accumulation and biochemical activation of both Rho and myosin II was coincident with the dynamics of neural tube formation. Inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 47 publications
9
118
0
5
Order By: Relevance
“…Consistent with regulation of cell shape via apical myosin activity, Kinoshita et al demonstrated Rho localization at the apical surface of the epithelium during chick neurulation, and connected some of its effects with pMRLC (Kinoshita et al, 2008). In the developing Drosophila eye, Myosin II regulates changes in both cell shape and cell clustering, and in spaghetti squash (MRLC mutant) and zipper (myosin heavy chain mutant) the apical surface does not constrict (Escudero et al, 2007;Hildebrand, 2005;Lee and Treisman, 2004).…”
Section: Research Articlementioning
confidence: 89%
“…Consistent with regulation of cell shape via apical myosin activity, Kinoshita et al demonstrated Rho localization at the apical surface of the epithelium during chick neurulation, and connected some of its effects with pMRLC (Kinoshita et al, 2008). In the developing Drosophila eye, Myosin II regulates changes in both cell shape and cell clustering, and in spaghetti squash (MRLC mutant) and zipper (myosin heavy chain mutant) the apical surface does not constrict (Escudero et al, 2007;Hildebrand, 2005;Lee and Treisman, 2004).…”
Section: Research Articlementioning
confidence: 89%
“…Increase of RhoB expression was unexpected because it was reported to be necessary for NC delamination (Liu and Jessell, 1998). However, it has recently been shown that Rho GTPases are widely expressed throughout the neural tube and that Rho overstimulation causes rounding of NE cells and apical extrusion into the lumen (Kinoshita et al, 2008). These observations suggest that Rho GTPases are involved in cytoskeleton stabilization during epithelial morphogenesis (Van Aelst and Symons, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In many vertebrate morphogenetic processes, Rok has been shown to act as an effector of the PCP pathway [40][41][42][43][44] . We therefore isolated and characterized the expression patterns of several genes encoding members of the PCP pathway in Platynereis.…”
Section: Cns Development Requires Rok-dependent Midline Formationmentioning
confidence: 99%